17.2% Efficient CdSexTe1−x solar cell with (InxGa1−x)2O3 emitter on lightweight and flexible glass - Jamarkattel, Manoj K.; Abbas, Ali; Mathew, Xavier; Neupane, Sabin; Bastola, Ebin; Li, Deng-Bing; Seibert, Samuel; Patel, Aesha P.; Song, Zhaoning; Liu, Xiaolei; Walls, John Michael; Garner, Sean M.; et al. (Applied physics letters, 2024)
High-efficiency, lightweight, and flexible solar cells are sought for a variety of applications particularly when high power density and flexible form factors are desired. Development of solar cells on flexible substrates may also offer production advantages in roll-to-roll or sheet-to-sheet processes. Here, we report device efficiencies of 17.2% and 14.6%, under AM1.5G and AM0 irradiances, respectively, for a flexible, lightweight, CdTe-based solar cell. To advance the efficiency relative to the highest previously reported AM1.5G value of 16.4%, we used an indium gallium oxide (IGO) emitter layer on a cadmium stannate (CTO) transparent conductor, which was deposited on 100-μm thick Corning® Willow® Glass. A sputtered CdSe layer was employed to incorporate Se into a CdTe absorber that was deposited by close-space sublimation, and CuSCN was used as a hole transport layer between the CdTe and the back metal electrode. The IGO and CTO layers remained intact during the high temperature film processing as seen in cross-sectional imaging and elemental mapping. This device configuration offers great promise for building-integrated photovoltaics, space applications, and higher rate manufacturing.